2020
DOI: 10.1111/asj.13452
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction from the first examination in clinical mastitis using ultrasonography in dairy cows

Abstract: The aim of this study was to examine whether ultrasonography can be used to predict the outcome of clinical mastitis in dairy cows. Forty-seven mastitic quarters of Holstein-Friesian cows were examined using ultrasonography at the time of the first examination. In mastitic mammary tissue, three sonographic signs indicating tissue abnormality were found: a hyperechoic spot in the parenchyma area, structural changes How to cite this article: Suzuki N, Kurose T, Kaneko S, Haraguchi A, Isobe N. Outcome prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The easy transfer of the ultrasound machine to the farm, the fast real-time imaging, and its application without the need for anesthetizing the animal [ 41 ] are reasons for its wide use ( Table 1 ). Ultrasonography has been proposed as a diagnostic technique for the diagnosis of subclinical mastitis in sheep [ 116 ] and as a tool indicating the proper time to start treatment [ 117 ] and also monitoring the progress of mastitis in cows [ 118 ]. After the ultrasonographic examination, microbiological examination and California mastitis test (CMT) of milk samples are employed to confirm the disease [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…The easy transfer of the ultrasound machine to the farm, the fast real-time imaging, and its application without the need for anesthetizing the animal [ 41 ] are reasons for its wide use ( Table 1 ). Ultrasonography has been proposed as a diagnostic technique for the diagnosis of subclinical mastitis in sheep [ 116 ] and as a tool indicating the proper time to start treatment [ 117 ] and also monitoring the progress of mastitis in cows [ 118 ]. After the ultrasonographic examination, microbiological examination and California mastitis test (CMT) of milk samples are employed to confirm the disease [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the utility of mammary ultrasound in identifying the presence of lesions or alterations of the mammary parenchyma and the teat, as well as in providing a valid indication of the outcome of treatment based on this evidence. Moreover, the possibility of pre-identifying animals for which intramammary antibiotic treatment could be ineffective would be an important element both in terms of antimicrobial resistance and for the economic impact of the disease itself [56][57][58][59]. The echographic examination of the mammary gland parenchyma in ruminant animals is performed primarily via the direct contact technique (transcutaneous echography).…”
Section: Mammary Ultrasoundmentioning
confidence: 99%
“…Udders were examined and classified according to on one or more of the following three signs: a hyperechoic spot in the parenchyma area, structural changes in the milk ducts, and non-homogenous parenchyma. According to the statistical analysis, only the presence of "non-homogeneous parenchyma" could be selected as a factor that predicts a marketable milk production [57]. The gland cisterns appear as a large homogenous anechoic area with few hypoechoic dots, which correspond to the milk [60].…”
Section: Mammary Ultrasoundmentioning
confidence: 99%